2010
DOI: 10.1002/ppap.200900164
|View full text |Cite
|
Sign up to set email alerts
|

Super‐Hydrophobic Coatings Prepared by RF Magnetron Sputtering of PTFE

Abstract: Fluorocarbon plasma polymer films were prepared by RF magnetron sputtering in Argon from a balanced magnetron equipped with polytetrafluoroethylene (PTFE) target. Depending on the deposition conditions, primarily on the working gas pressure and distance between the target and the substrate, plasma polymer films were obtained with distinctly different chemical composition and/or morphology, as measured by means of XPS, FTIR and AFM. These films possessed static contact angle of water values ranging from 112° to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(41 citation statements)
references
References 28 publications
2
39
0
Order By: Relevance
“…The selection of these two materials was made on the basis of previous works that indicated that fluorocarbons have, in contrast to sputtered nylon that is rich in oxygen and nitrogen functional groups, very low condensation coefficient for metal atoms [31]. The deposition of these two plasma polymers was performed in plasma reactors described in more detail in previous studies [32,33]. RF planar, water cooled magnetron equipped with either PTFE or nylon 6,6 target, both sourced from Goodfellow, was used in both cases.…”
Section: Substrate Materialsmentioning
confidence: 99%
“…The selection of these two materials was made on the basis of previous works that indicated that fluorocarbons have, in contrast to sputtered nylon that is rich in oxygen and nitrogen functional groups, very low condensation coefficient for metal atoms [31]. The deposition of these two plasma polymers was performed in plasma reactors described in more detail in previous studies [32,33]. RF planar, water cooled magnetron equipped with either PTFE or nylon 6,6 target, both sourced from Goodfellow, was used in both cases.…”
Section: Substrate Materialsmentioning
confidence: 99%
“…The latter enabled production of complex functional nanocomposite or nanostructured materials with different architectures including classical nanocomposites or multi‐layered structures, coatings with dual‐scale roughness, or materials with horizontal gradients of NPs embedded into a matrix material . Furthermore, the GAS systems were proved to be highly flexible also in terms of composition of produced NPs as they enabled fabrication of metallic, metal‐oxide as well as polymeric NPs …”
Section: Introductionmentioning
confidence: 99%
“…In the past, many researchers have tried to improve the hydrophobicity of solid film by radio frequency (RF) magnetron sputtering [19]. Barshiilia et.al prepared three types of ZnO based coatings and analyzed the effect of surface morphology on the wettability [20].…”
Section: Introductionmentioning
confidence: 99%